THE EFFECT OF SHADOWING APPLICATION TOWARDS STUDENT SPEAKING SKILL AT THE TENTH GRADE STUDENTS' OF SMAN 6 PANDEGLANG IN ACADEMIC YEAR 2023/2024 - Ema Rohmatul fazriyah; Ari Fajria Novari; Tatu Munawaroh (Aisyah Journal of English Language Teaching (AIJELT), 2024)
The goal of the study is to determine whether using a shadowing application significantly improves students' speaking abilities in the tenth grade students’ at SMAN 6 Pandeglang. Using a pre-test and post-test group design, the methodology is quasi-experimental, and the study methodology is quantitative. There are 350 students in the population of this study, and there are 70 students in the sample. The statistical analysis of the data was conducted using the IBM SPSS 29 software. Based on the data analysis results, it is evident that the tenth-grade students of SMAN 6 Pandeglang benefit significantly from the shadowing approach in terms of their speaking abilities. The t-test findings show that the obtained sig value was less than or equal to 0.05 The statistics clearly shows that using the shadowing Application improves the speaking ability of SMAN 6 Pandeglang students’ in the tenth grade.